Nanoparticles as Immune Modulatory Reagents for Production of Rift Valley Fever Hyperimmune Serum in Sheep - Yehia H, Marwa; Abulmagd, Diana M.; Atwa , Mohamed H.; Ezz El-Deen, Noha; Abd El-Fattah, Taradi (Journal of Advanced Veterinary Research, 2023)
Rift Valley Fever (RVF) since its discovery has been recognized as a source of numerous outbreaks in Africa and Arab peninsulas. It is a zoonotic highly pathogenic mosquito born virus disease. The first line of defense against such disease is the prevention of its the occurrence by periodic vaccination. The use of adjuvant is of fundamental importance in vaccines formulations and hyperimmune serum production. This study aimed to prepare hyperimmune serum against RVF virus to be used in diagnostic purposes in addition to its possible use for treatment in emergence cases. To establish this goal, we use Montanide IMS 3015 investigating its immune modulatory effect in immunized sheep. The experimental sheep received 3 injections of inactivated RVF virus adjuvant with Montanide IMS 3015 one week intervals, the fourth injection was virulent virus. The obtained serum 7 days after the last injection was discovered to be safe and free of foreign pollutants. For mice; specific for RVF virus with mean serum neutralizing antibody titer 20480 and ELISA optical density 1.402. It was found that this serum was able to protect mice against experimental infection with RVF virus in the ratios 100%; 100%; 90% and 60% of it was administrated to mice 24 hours pre-virus infection; simultaneously with the virus; 24 hours post-infection and 48 hours post infection respectively while later serum administration was unable to protect mice against viral infection.